2006
DOI: 10.1007/s10802-005-9018-3
|View full text |Cite
|
Sign up to set email alerts
|

WISC-R Subtest But No Overall VIQ–PIQ Difference in Dutch Children with PDD-NOS

Abstract: VIQ-PIQ differences have been studied in children with autism and Asperger syndrome but have not been studied in a separate group of children with PDD-NO, although, PDD-NOS has a much higher prevalence rate than autism and deficits in communication and social interaction are severe. The Wechsler Intelligence Scale for Children-Revised (WISC-R) was administered to 100 children, aged 6-12 years, with PDD-NOS (n = 76), autism (n = 13), and Asperger syndrome (n = 11). PDD-NOS was diagnosed using explicit research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
39
2

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 17 publications
5
39
2
Order By: Relevance
“…Thus, from a clinical standpoint, children whose PDD-NOS diagnosis was established before 36 months should be re-assessed at a later age (Rondeau et al, 2010). Similar to previous reports (Allen et al, 2001, deBruin et al, 2006, Matson, et al, 2007, Szatmari et al 2002, in our study (Karabekiroglu & Akbas, in press) mental retardation was significantly more prevalent in the autism than in the PDD-NOS or ADHD groups. Several investigators suggested that exploring the presence of mental retardation may be more useful in terms of planning treatment and predicting outcome than a classification based on symptom number alone (Szatmari et al, 2002).…”
Section: Discussionsupporting
confidence: 88%
“…Thus, from a clinical standpoint, children whose PDD-NOS diagnosis was established before 36 months should be re-assessed at a later age (Rondeau et al, 2010). Similar to previous reports (Allen et al, 2001, deBruin et al, 2006, Matson, et al, 2007, Szatmari et al 2002, in our study (Karabekiroglu & Akbas, in press) mental retardation was significantly more prevalent in the autism than in the PDD-NOS or ADHD groups. Several investigators suggested that exploring the presence of mental retardation may be more useful in terms of planning treatment and predicting outcome than a classification based on symptom number alone (Szatmari et al, 2002).…”
Section: Discussionsupporting
confidence: 88%
“…The fact that this particular pattern of subtest scores was present in our PDD-NOS group strengthens the credibility of the findings and the accuracy of the PDD-NOS diagnoses. Absolute good performance by PDD-NOS children on Mazes (but not on Block Design this time) was found by De Bruin et al (2006). It can be concluded that in the IQ range of above 70, PDD-NOS children perform better than ADHD children and those with a combined diagnosis, which can primarily be attributed to differences in visuospatial and visuomotor abilities among the groups.…”
Section: Resultsmentioning
confidence: 81%
“…Up to this date, only two articles described the profiles of cognitive functioning in children with PDD-NOS (De Bruin et al 2006;Koyama et al 2006). The latter of these two also made a comparison with ADHD children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…But some PDD children are often misdiagnosed with non-PDD conditions, such as attention-deficit-hyperactivity disorder (ADHD). 2 The Wechsler intelligence scales (Wechsler Intelligence Scale for Children [WISC], Wechsler Adult Intelligence Scale [WAIS]) are familiar cognitive tests, and because some of the characteristics have been identified in PDD children, such as a high score on Block Design or a low score on Comprehension, [3][4][5][6][7] information from those subtests may be useful to differentiate PDD children from non-PDD ones. Mayes and Calhoun classified each child's WISC-III profile type by ranking the index and the subtest scores from lowest to highest, and found that low Coding with low Comprehension or low Freedom from Distractibility index with low Comprehension profile correctly identified 56% of children with high-functioning (IQ Ն 80) autism and 76% without autism.…”
mentioning
confidence: 99%